(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
This thesis addresses questions such as: How should the religion of Islam relate to innovations in the world? And also, Does Islam accept globalization and how does it react to it? This thesis reveals the opinions of various scholars from the Islamic world regarding globalization.